Pemanfaatan Media dan Teknik Pembelajaran yang Menyenangkan untuk Pembelajaran Bahasa Inggris di SDK Roworeke 2 - Stefanus Tebajak Henakin; Maria Yasinta Ome; Maria Alfira Fe’a; Maria Adelheid Bayan Makin (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
Mastery of English as an international language is an international language is an important need in the word of education, including at the elementary school level. However, the monotonous and less varied learning processes often causes low interest and motivation of students in learning English. This Community Service Activity (PKM) was carried out in class V at SDN Roworeke 2 with 11 students which aims to improve the quality of English learning trough the use of media and fun learning techniques. The methods used included demonstration, question and answer methods as well as the use of activite learning techniques such as educational games and songs. The result of the activity showed an uncrease in student enthusiasm and participation in learning, this activity was also able to increase interest and motivation in learning English.